2020
DOI: 10.1111/os.12753
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sagittal Insertion Depth and Direction of Femoral Intramedullary Rod in Total Knee Arthroplasty in Chinese Osteoarthritis Patients

Abstract: Objective To identify the optimal femoral intramedullary rod insertion depth and direction on the sagittal plane in total knee arthroplasty (TKA) of Chinese osteoarthritis (OA) patients. Methods From January to December 2019, CT data were collected for 85 consecutive entire lower extremity Chinese OA patients. A three‐dimensional method was used to simulate intramedullary rod penetration. The intramedullary rods were inserted toward the anterior (TA), center (TC), and posterior (TP) of the femoral canal, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…At the same time shows no statistical significance among various length of lengths. 8 It was found that three-degree varus and valgus alignment of TKR femoral implant does give best stability. 9 In our study we found that maximum samples inside this three-degree varus and valgus as shown in table no.5.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time shows no statistical significance among various length of lengths. 8 It was found that three-degree varus and valgus alignment of TKR femoral implant does give best stability. 9 In our study we found that maximum samples inside this three-degree varus and valgus as shown in table no.5.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time shows no statistical significance among various length of lengths. 8 It was found that three-degree varus and valgus alignment of TKR femoral implant does give best stability. 9 In our study we found that maximum samples inside this three-degree varus and valgus as shown in table no.5.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal positioning of the femoral component in the sagittal plane has not yet been defined [ 13 , 14 ]. Surgeons using navigation, for sagittal positioning of femoral component, continue to make the distal femoral cut perpendicular to SMX [ 8 , 9 ], although studies have shown that this can increase the risk of notching in navigated TKA [ 6 , 12 ].…”
Section: Discussionmentioning
confidence: 99%